Mourning in Ptolemaic and Roman Egyptian Art: The Lamentations of Isis and Nephthys - Izquierdo Perales, Alejandra (Eikón / Imago, 2024)
This work aims to study the iconography of crying of Isis and Nephthys in combination with the funerary literature of the Ptolemaic and Roman period in which evidence related to the grief of the Two Sisters is attested. Although the grief of both goddesses over the death of Osiris was not restricted to the funerary literature of the Ptolemaic period, it seems that it was then that this theme was developed in greater detail. In order to carry out this study, the texts of The Glorifications, among which are those known as The Lamentations of Isis and Nephthys, have been taken into account alongside the representations of Isis and Nephthys in different objects found in funerary contexts. The iconography of the two goddesses shows allusions to funerary texts, the use of weeping as a ritual component to guarantee the survival of the deceased person in the Hereafter. It also emphasizes the identification of the dead with Osiris through the plastic art representations and funeral rituals.